Measuring and reporting biodiversity change. (September 2017) - Turak, Eren; Regan, Eugenie; Costello, Mark John
Abstract: Efforts to halt the loss of biodiversity and degradation of ecosystem services are difficult to evaluate because of the lack of reliable measures of the state of local, national, regional, and global biodiversity. This special issue contains 11 papers that review and advance the field of biodiversity measurement, including thematic gaps and global priorities, making full use of all data sources and opportunities, the importance of indices and metrics, linkages to management, and reporting biodiversity change. This body of work is an important contribution to the ongoing efforts to take the measurement of biodiversity from an uncoordinated and disparate situation to a harmonised framework that is scalable, flexible, pragmatic, and ready to inform management. These papers describe advances in this field but they also highlight the important challenges that remain, including consensus on the most important measures, the filling of thematic gaps, and communicating biodiversity change to wider audiences.